Hard carbon negative electrode material and preparation method thereof, nitrogen-containing asphalt coating and sodium ion battery
By performing nitrogen doping treatment on asphalt and uniform mixing with biomass powder, the problems of low first charge and discharge efficiency and uneven coating of biomass-based hard carbon negative electrode materials are solved, and the hydrophobicity and circulation performance of the material are improved, thus achieving the realization of the water-repellent and cyclic properties of the material. Higher specific capacity and rate performance.
Patent Information
- Application Number
- CN202411385604.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-30
AI Technical Summary
In the prior art, the first charge and discharge efficiency of the biomass-based hard carbon negative electrode material is low, and the asphalt coating method has problems of powder agglomeration and uneven coating, which affects the specific capacity and rate performance of the material.
By doping the asphalt nitrogen, a nitrogen-containing asphalt coating is obtained, and mixed with the pre-carbonized biomass powder and then sintered to form a hard carbon negative electrode material, which improves the hydrophobicity of the material and the rapid migration of sodium ions ability.
The first charge and discharge efficiency and cyclic performance of the material are improved, powder agglomerated, and a highly graphitized hydrophobic coating is formed, which enhances the specific capacity and rate performance of the material.
Smart Images

Figure CN119284874A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of new energy materials, and in particular relates to a hard carbon negative electrode material and a preparation method thereof, a nitrogen-containing asphalt coating, and a sodium ion battery. Background Art
[0002] Biomass-based hard carbon has the advantages of wide raw material sources, low cost, and high specific capacity. It is the most promising negative electrode material for sodium-ion batteries, but it is still limited by its low initial charge and discharge efficiency. Biomass is rich in oxygen, and its derived hard carbon inevitably contains a large number of oxygen-containing functional groups and has good hydrophilicity. The negative electrode is generally made of water-based slurry. The material absorbs water, which will cause a large amount of gas to be generated during the battery cycle, which will damage the battery cycle life and bring safety hazards.
[0003] The existing technology uses asphalt to coat the negative electrode powder to further improve the electrochemical performance and reduce the hydrophilicity of the material. However, the carbonization of asphalt at a low temperature has a lot of defects and cannot meet the requirements of improving the initial charge and discharge efficiency. The high-temperature sintering has a high degree of graphitization and the sodium ions cannot be quickly embedded, which has a significant negative impact on the material's specific capacity and rate performance. At the same time, direct coating of the carbonized material has the problem of powder agglomeration and uneven coating. Summary of the invention
[0004] In view of this, an embodiment of the present application provides a method for preparing a hard carbon negative electrode material, which aims to solve the problems of powder agglomeration, uneven coating, and inability to meet the requirements for improving the initial charge and discharge efficiency in the existing method of using asphalt to coat the negative electrode powder, and a significant negative impact on the material's specific capacity and rate performance.
[0005] A first aspect of an embodiment of the present application provides a method for preparing a hard carbon negative electrode material, comprising:
[0006] Performing nitrogen doping treatment on asphalt to obtain nitrogen-containing asphalt coating;
[0007] The pre-carbonized biomass powder and the nitrogen-containing asphalt coating are evenly mixed, and the obtained mixed powder is sintered to obtain a hard carbon negative electrode material.
[0008] In a possible implementation of the first aspect, the nitrogen-doping treatment of asphalt to obtain the nitrogen-containing asphalt coating includes:
[0009] After the asphalt is crushed, it is treated with plasma to obtain a nitrogen-containing asphalt coating;
[0010] In the plasma treatment, the nitrogen gas flow rate is 40-100 mL / min, the power is 200-300 W, the reaction temperature is 25-300° C., and the treatment time is 1-2 h.
[0011] In another possible implementation of the first aspect, the nitrogen-doping treatment of asphalt to obtain the nitrogen-containing asphalt coating includes:
[0012] The asphalt is mixed with a nitrogen source and then subjected to heat treatment to obtain a nitrogen-containing asphalt coating;
[0013] The amount of nitrogen source is 2-10%, the heat treatment temperature is 200-280° C., and the heat treatment time is 3-6 hours.
[0014] In another possible implementation of the first aspect, the nitrogen-doping treatment of asphalt to obtain the nitrogen-containing asphalt coating includes:
[0015] The asphalt is mixed with a nitrogen source and then ball-milled, or the asphalt is placed in a nitrogen-containing gas atmosphere and ball-milled to obtain a nitrogen-containing asphalt coating; wherein the nitrogen source amount is 2-10%, the nitrogen source amount is 2-10%; when the nitrogen source amount is 2-5%, the ball-milling time is 6-24h, and when the nitrogen source amount is 5-10%, the ball-milling time is 6-12h.
[0016] A second aspect of an embodiment of the present application provides a hard carbon negative electrode material, wherein the hard carbon negative electrode material is prepared by the preparation method of the hard carbon negative electrode material described in the first aspect above.
[0017] A third aspect of an embodiment of the present application provides a nitrogen-containing asphalt coating as described in the first aspect above.
[0018] A fourth aspect of an embodiment of the present application provides a sodium ion battery, characterized in that the sodium ion battery comprises the hard carbon negative electrode material described in the above second aspect.
[0019] The preparation method of the hard carbon negative electrode material provided in the embodiment of the present application performs nitrogen doping treatment on asphalt so that the asphalt has a larger carbon layer spacing after high-temperature sintering, which can provide sodium storage sites and facilitate the rapid migration of sodium ions, while improving the initial charge and discharge efficiency and hydrophobicity of the material without affecting the specific capacity and rate performance; in addition, the biomass precursor has a rich open pore structure and a large specific surface area after pre-carbonization, and high-speed mixing with the coating is more conducive to the uniform adsorption of small particles of the coating on the main material, reducing powder agglomeration, and the rich carbon and hydrogen elements in the asphalt during the high-temperature sintering process can reduce the oxygen-containing functional groups in the pre-carbonized precursor, and the highly graphitized coating layer formed has stronger hydrophobicity and fewer defect sites, and at the same time transforms the open pore structure into a closed pore structure, thereby improving the initial charge and discharge efficiency, specific capacity and cycle performance of the material as a negative electrode of a sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The first charge and discharge curve diagram of the hard carbon negative electrode material provided in Comparative Example 1 of the present application;
[0021] Figure 2 The first charge and discharge curve diagram of the hard carbon negative electrode material provided in Comparative Example 2 of the present application;
[0022] Figure 3 The first charge and discharge curve diagram of the hard carbon negative electrode material provided in Comparative Example 3 of the present application;
[0023] Figure 4 The first charge and discharge curve diagram of the hard carbon negative electrode material provided in Example 1 of the present application;
[0024] Figure 5 This is a first charge and discharge curve diagram of the hard carbon negative electrode material provided in Example 7 of the present application;
[0025] Figure 6 This is a first charge and discharge curve diagram of the hard carbon negative electrode material provided in Example 12 of the present application. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0027] The present invention provides a method for preparing a hard carbon negative electrode material, comprising the following steps:
[0028] Step S1: performing nitrogen doping treatment on asphalt to obtain a nitrogen-containing asphalt coating.
[0029] In the embodiment of the present application, the asphalt is crushed at high speed and then nitrogen-doped to obtain a nitrogen-containing asphalt coating; the particle size distribution of the crushed asphalt is D 50 The nitrogen doping method includes but is not limited to plasma treatment, chemical nitrogen doping and physical mechanical nitrogen doping.
[0030] Preferably, the plasma nitrogen doping treatment method is: after the asphalt is crushed, it is placed in a plasma chamber, high-purity nitrogen is introduced at a gas flow rate of 40-100 mL / min, the power is 200-300 W, the reaction temperature is 25-300° C., the heating rate is 2-5° C. / min, and the plasma treatment is performed for 1-2 hours to obtain a nitrogen-containing asphalt coating. The plasma instrument model used in the embodiment of the present application is FURNACE 1200.
[0031] Preferably, the chemical nitrogen doping treatment method is: mixing asphalt with a nitrogen-containing compound and then heat treating it to obtain a nitrogen-containing asphalt coating. The nitrogen source is preferably 2-10%, that is, the mass ratio of asphalt to nitrogen-containing compound is 10:(0.2-1); the nitrogen-containing compound can be urea, ammonium carbonate, ammonium nitrate, etc.; the heat treatment temperature is 200-280°C, and the heat treatment time is 3-6h.
[0032] Preferably, the physical and mechanical nitrogen doping treatment method is: after mixing the asphalt with the nitrogen-containing compound, ball milling is performed, or the asphalt is ball milled in a nitrogen-containing gas atmosphere to obtain a nitrogen-containing asphalt coating. Wherein, the nitrogen source is a nitrogen-containing compound or a nitrogen-containing gas, and the amount of the nitrogen source is preferably 2-10%, that is, the mass ratio of the asphalt to the nitrogen-containing compound is 10: (0.2-1); the nitrogen-containing compound can be urea, ammonium carbonate, ammonium nitrate, etc., and the nitrogen-containing gas can be nitrogen, ammonia, etc.; during the ball milling process, the ball-to-material ratio is (500-200):50, and the ball milling speed is 400-600r / min; when the nitrogen source amount is 2-5%, the ball milling time is 6-24h, and when the nitrogen source amount is 5-10%, the ball milling time is 6-12h.
[0033] It is worth noting that the present application first nitrogen-doped the asphalt and then performed the subsequent coating treatment, which would not damage the coating layer and could better protect the hard carbon material itself compared to the method of first coating and then nitrogen-doping. The present application can achieve nitrogen doping through the above-mentioned plasma treatment, or chemical nitrogen doping, or physical and mechanical nitrogen doping treatment, so that the asphalt has a larger carbon layer spacing after high-temperature sintering, can provide sodium storage sites, and is conducive to the rapid migration of sodium ions, while improving the initial charge and discharge efficiency and hydrophobicity of the material without affecting the specific capacity and rate performance.
[0034] Among them, during the plasma treatment process, when the nitrogen source amount is increased from 2% to 15%, or the gas flow rate is gradually increased from 40mL / min to 150mL / min, or the plasma power is gradually increased from 200W to 400W, or the treatment temperature is gradually increased from 25°C to 400°C, or the treatment time is gradually increased from 1h to 4h, the nitrogen content of the hard carbon gradually increases, the uniformity of the coating thickness deteriorates, and the disorder degree is too large, resulting in a gradual decrease in the first coulomb efficiency of the obtained product and a gradual deterioration in the hydrophobic performance. Therefore, the gas flow rate is preferably 40-100mL / min, the power is preferably 200-300W, the temperature is preferably 25-300°C, and the time is preferably 1-2h.
[0035] During the chemical nitrogen doping treatment, when the nitrogen source amount is increased from 2% to 15%, or the temperature is increased from 200°C to 400°C, or the treatment time is increased from 3h to 12h, the nitrogen content of the hard carbon gradually increases, the uniformity of the coating thickness deteriorates, and the disorder degree is excessive, resulting in a gradual decrease in the first coulomb efficiency of the obtained product and a gradual deterioration in the hydrophobic performance. Therefore, the nitrogen source amount is preferably 2%-10%, the temperature is preferably 200°C-280°C, and the treatment time is preferably 3-6h.
[0036] During the physical ball milling nitrogen doping process, when the nitrogen source amount is increased from 2% to 15%, or when the nitrogen source amount is 5-10% and the treatment time is increased from 6h to 24h, the nitrogen content of the hard carbon gradually increases, the uniformity of the coating thickness deteriorates, and the disorder degree is too large, resulting in a gradual decrease in the first coulomb efficiency of the obtained product and a gradual deterioration in the hydrophobic performance. Therefore, the nitrogen source amount is preferably 2%-10%; when the nitrogen source amount is 5-10%, the treatment time is preferably 6-12h.
[0037] Step S2: Evenly mix the pre-carbonized biomass powder and the nitrogen-containing asphalt coating, and sinter the obtained mixed powder to obtain a hard carbon negative electrode material.
[0038] In the embodiment of the present application, the mass ratio of the pre-carbonized biomass powder to the nitrogen-containing asphalt coating is 10:(0.2-1). According to the structural characterization, the coating thickness of the negative electrode material is 0.2-100 nm.
[0039] In the embodiment of the present application, before the step of uniformly mixing the pre-carbonized biomass powder with the nitrogen-containing asphalt coating, sintering the obtained mixed powder, and obtaining the hard carbon negative electrode material, the method includes: placing the biomass in an inert gas atmosphere, pre-carbonizing at a temperature of 400-800°C for 2-6 hours, and then crushing it. Among them, the biomass can be bamboo stems, wood stems, etc. Although the embodiment of the present application only uses bamboo stems as an example, it should not be used to limit the scope of protection of the present application. Based on the present application, those skilled in the art can think of using other biomass materials to replace the bamboo stems in the embodiment. The inert gas can be argon or nitrogen, and the heating rate can be 2-5°C / min; the particle size distribution D50 of the pre-carbonized biomass after crushing is 5-10um. After pre-carbonization, the biomass precursor has a rich open pore structure and a large specific surface area, which is more conducive to the uniform adsorption of small particles of the coating under high-speed mixing and reduces powder agglomeration.
[0040] In an embodiment of the present application, the mixed powder obtained is sintered to obtain a hard carbon negative electrode material, comprising: placing the mixed powder in an inert gas atmosphere, and sintering it at a temperature of 1100 to 1500°C for 2-6 hours to obtain a hard carbon negative electrode material. The inert gas may be argon or nitrogen, and the heating rate may be 2-10°C / min. During the high-temperature sintering process, the carbon and hydrogen elements rich in asphalt can reduce the oxygen-containing functional groups in the pre-carbonized precursor, and the highly graphitized coating layer formed has stronger hydrophobicity and fewer defect sites, while converting the open pore structure into a closed pore structure, thereby improving the material's initial charge and discharge efficiency, specific capacity, and cycle performance.
[0041] The nitrogen-containing asphalt coating, hard carbon negative electrode material, and sodium ion battery are described in detail in the following specific examples, as shown below. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are all commercially available unless otherwise specified.
[0042] Example 1
[0043] The method for preparing the nitrogen-containing asphalt coating and the hard carbon negative electrode material provided in this embodiment comprises the following steps:
[0044] Step S1: Take 100 g of bamboo stems, peel them, and then mechanically crush them into powder, pass them through a 100-mesh sieve, and dry them in a forced air drying oven at 80° C. for 12 h to obtain a bamboo powder precursor.
[0045] Step S2: pre-carbonize the bamboo powder obtained in step S1 in a box furnace at a carbonization temperature of 600°C, a heating rate of 100°C / h, a holding time of 2h, an argon atmosphere, and naturally cool to obtain about 30g of pre-carbonized precursor.
[0046] Step S3: The pre-carbonized precursor obtained in step S2 is crushed at high speed to control the particle size distribution D50 to 5 um.
[0047] Step S4: crushing the petroleum asphalt at high speed to control the particle size distribution D50 to 2 um.
[0048] Step S5: Put the asphalt obtained in step S4 into a plasma chamber, introduce high-purity nitrogen at a rate of 40 mL / min, with a plasma power of 200 W, and keep warm at 280° C. for 2 h to obtain a nitrogen-containing asphalt coating.
[0049] Step S6: Take 20 g of the pre-carbonized precursor prepared in step S3 and 1 g of the nitrogen-containing asphalt coating obtained in step S5 and mix them at high speed.
[0050] Step S7: sinter the mixed powder obtained in step S5 at high temperature in a tube furnace, the sintering temperature is 1300°C, the heating rate is 100°C / h, the atmosphere is argon, the insulation time is 2h, and the hard carbon negative electrode material is obtained by natural cooling.
[0051] Example 2
[0052] The experimental steps were the same as in Example 1, but the plasma chamber was kept at room temperature.
[0053] Example 3
[0054] The experimental steps were the same as in Example 1, but high purity nitrogen was introduced at a rate of 100 mL / min.
[0055] Example 4
[0056] The experimental steps are the same as in Example 1, but the plasma power is 300W.
[0057] Example 5
[0058] The experimental steps were the same as in Example 1, but the plasma holding time was 1 h.
[0059] Example 6
[0060] The experimental steps were the same as in Example 1, but high-purity nitrogen was introduced at a rate of 80 mL / min.
[0061] Example 7
[0062] The experimental steps were the same as in Example 1, but the plasma chamber temperature was maintained at 200°C.
[0063] Example 8
[0064] The method for preparing the nitrogen-containing asphalt coating and the hard carbon negative electrode material provided in this embodiment comprises the following steps:
[0065] Step S1: Take 100 g of bamboo stems, peel them, and then mechanically crush them into powder, pass them through a 100-mesh sieve, and dry them in a forced air drying oven at 80° C. for 12 h to obtain a bamboo powder precursor.
[0066] Step S2: pre-carbonize the bamboo powder obtained in step S1 in a box furnace at a carbonization temperature of 600°C, a heating rate of 100°C / h, a holding time of 2h, an argon atmosphere, and naturally cool to obtain about 30g of pre-carbonized precursor.
[0067] Step S3: The pre-carbonized precursor obtained in step S2 is crushed at high speed to control the particle size distribution D50 to 5 um.
[0068] Step S4: petroleum asphalt and urea are mixed in a mass ratio of 50:1, placed in a ball mill, with a ball-to-material ratio of 250:50, and ball milled for 12 hours. After the ball milling is completed, the mixture is taken out and crushed at a high speed, and the particle size distribution D50 is 2 um.
[0069] Step S5: Take 20 g of the pre-carbonized precursor prepared in step S3 and 1 g of the nitrogen-containing asphalt coating obtained in step S4 and mix them at high speed.
[0070] Step S6: sinter the mixed powder obtained in step S5 at high temperature in a tubular furnace, the sintering temperature is 1300°C, the heating rate is 100°C / h, the atmosphere is argon, the insulation time is 2h, and the hard carbon negative electrode material is obtained by natural cooling.
[0071] Example 9
[0072] The experimental steps were the same as those in Example 8, except that petroleum asphalt and urea were mixed at a mass ratio of 20:1.
[0073] Example 10
[0074] The experimental steps were the same as those in Example 8, except that petroleum asphalt and urea were mixed in a mass ratio of 10:1.
[0075] Embodiment 11
[0076] The experimental steps were the same as in Example 9, but the ball milling time was 6 h.
[0077] Example 12
[0078] The experimental steps were the same as in Example 9, but the ball milling time was 24 h.
[0079] Embodiment 13
[0080] The method for preparing the nitrogen-containing asphalt coating and the hard carbon negative electrode material provided in this embodiment comprises the following steps:
[0081] Step S1: Take 100 g of bamboo stems, peel them, and then mechanically crush them into powder, pass them through a 100-mesh sieve, and dry them in a forced air drying oven at 80° C. for 12 h to obtain a bamboo powder precursor.
[0082] Step S2: pre-carbonize the bamboo powder obtained in step S1 in a box furnace at a carbonization temperature of 600°C, a heating rate of 100°C / h, a holding time of 2h, an argon atmosphere, and naturally cool to obtain about 30g of pre-carbonized precursor.
[0083] Step S3: The pre-carbonized precursor obtained in step S2 is crushed at high speed to control the particle size distribution D50 to 5 um.
[0084] Step S4: petroleum asphalt and urea are mixed in a mass ratio of 50:1, and heat treated in a tubular furnace under an argon atmosphere for 3 hours at a temperature of 280°C and a heating rate of 5°C / min. After natural cooling, they are crushed at high speed, and the particle size distribution D50 is 2 um.
[0085] Step S5: Take 20 g of the pre-carbonized precursor prepared in step S2 and 1 g of the nitrogen-containing asphalt coating obtained in step S4 and mix them at high speed.
[0086] Step S6: sinter the mixed powder obtained in step S5 at high temperature in a tubular furnace, the sintering temperature is 1300°C, the heating rate is 100°C / h, the atmosphere is argon, the insulation time is 2h, and the hard carbon negative electrode material is obtained by natural cooling.
[0087] Embodiment 14
[0088] The experimental steps were the same as those in Example 8, except that petroleum asphalt and urea were mixed at a mass ratio of 20:1.
[0089] Embodiment 15
[0090] The experimental steps were the same as those in Example 8, except that petroleum asphalt and urea were mixed in a mass ratio of 10:1.
[0091] Example 16
[0092] The experimental steps are the same as those in Example 14, but the heat treatment time is 6 h.
[0093] Embodiment 17
[0094] The experimental steps are the same as those in Example 14, but the heat treatment temperature is 250°C.
[0095] Embodiment 18
[0096] The experimental steps are the same as those in Example 14, but the heat treatment temperature is 200°C.
[0097] Embodiment 19
[0098] The experimental steps are the same as those in Example 1, but step S6 is: taking 20 g of the pre-carbonized precursor prepared in step S3 and 0.4 g of the nitrogen-containing asphalt coating obtained in step S5 and mixing them at high speed.
[0099] Embodiment 20
[0100] The experimental steps are the same as those in Example 1, but step S6 is: taking 20 g of the pre-carbonized precursor prepared in step S3 and 2 g of the nitrogen-containing asphalt coating obtained in step S5 and mixing them at high speed.
[0101] Comparative Example 1
[0102] The method for preparing the hard carbon negative electrode material provided in this embodiment comprises the following steps:
[0103] Step S1: Take 100 g of bamboo stems, peel them, and then mechanically crush them into powder, pass them through a 100-mesh sieve, and dry them in a forced air drying oven at 80° C. for 12 h to obtain a bamboo powder precursor.
[0104] Step S2: pre-carbonize the bamboo powder obtained in step S1 in a box furnace at a carbonization temperature of 600°C, a heating rate of 100°C / h, a holding time of 2h, an argon atmosphere, and naturally cool to obtain about 35g of pre-carbonized precursor.
[0105] Step S3: The pre-carbonized precursor obtained in step S2 is sintered at high temperature in a tubular furnace, the sintering temperature is 1300°C, the atmosphere is argon, the heating rate is 100°C / h, the insulation time is 2h, and naturally cooled to obtain about 25g of hard carbon negative electrode material.
[0106] Step S4: crushing the hard carbon negative electrode material obtained in step S3 at high speed to control the particle size distribution D50 to 5 um.
[0107] Comparative Example 2
[0108] The method for preparing the hard carbon negative electrode material provided in this embodiment comprises the following steps:
[0109] Step S1: Take 100 g of bamboo stems, peel them, and then mechanically crush them into powder, pass them through a 100-mesh sieve, and dry them in a forced air drying oven at 80° C. for 12 h to obtain a bamboo powder precursor.
[0110] Step S2: pre-carbonize the bamboo powder obtained in step S1 in a box furnace at a carbonization temperature of 600°C, a heating rate of 100°C / h, a holding time of 2h, an argon atmosphere, and naturally cool to obtain about 35g of pre-carbonized precursor.
[0111] Step S3: The pre-carbonized precursor obtained in step S2 is sintered at high temperature in a tubular furnace at a sintering temperature of 1300°C, a heating rate of 100°C / h, an argon atmosphere, a holding time of 2h, and natural cooling to obtain about 25g of hard carbon material.
[0112] Step S4: crushing the hard carbon material obtained in step S3 at high speed to control the particle size distribution D50 to 5 um.
[0113] Step S5: crushing the petroleum asphalt at high speed to control the particle size distribution D50 to 2 um.
[0114] Step S6: Take 20 g of the pre-carbonized precursor prepared in step S4 and 1 g of the asphalt obtained in step S5 and mix them at high speed.
[0115] Step S7: sinter the mixed powder obtained in step S6 at high temperature in a tube furnace, the sintering temperature is 800°C, the heating rate is 100°C / h, the atmosphere is argon, the insulation time is 2h, and the hard carbon negative electrode material is obtained by natural cooling.
[0116] Comparative Example 3
[0117] The method for preparing the hard carbon negative electrode material provided in this embodiment comprises the following steps:
[0118] Step S1: Take 100 g of bamboo stems, peel them, and then mechanically crush them into powder, pass them through a 100-mesh sieve, and dry them in a forced air drying oven at 80° C. for 12 h to obtain a bamboo powder precursor.
[0119] Step S2: pre-carbonize the bamboo powder obtained in step S1 in a box furnace at a carbonization temperature of 600°C, a heating rate of 100°C / h, a holding time of 2h, an argon atmosphere, and naturally cool to obtain about 30g of pre-carbonized precursor.
[0120] Step S3: The pre-carbonized precursor obtained in step S2 is crushed at high speed to control the particle size distribution D50 to 5 um.
[0121] Step S4: crushing the petroleum asphalt at high speed to control the particle size distribution D50 to 2 um.
[0122] Step S5: Take 20 g of the pre-carbonized precursor prepared in step S3 and 1 g of the asphalt obtained in step S4 and mix them at high speed.
[0123] Step S6: sinter the mixed powder obtained in step S5 at high temperature in a tubular furnace, the sintering temperature is 1300°C, the heating rate is 100°C / h, the atmosphere is argon, the insulation time is 2h, and the hard carbon negative electrode material is obtained by natural cooling.
[0124] Comparative Example 4
[0125] The experimental steps were the same as in Example 1, but the plasma chamber temperature was maintained at 400°C.
[0126] Comparative Example 5
[0127] The experimental steps were the same as in Example 1, but high purity nitrogen was introduced at a rate of 150 mL / min.
[0128] Comparative Example 6
[0129] The experimental steps are the same as in Example 1, but the plasma power is 400W
[0130] Comparative Example 7
[0131] The experimental steps were the same as in Example 1, but the plasma holding time was 4 h.
[0132] Comparative Example 8
[0133] The experimental steps were the same as in Example 10, but the ball milling time was 24 h.
[0134] Comparative Example 9
[0135] The experimental steps were the same as those in Example 9, except that petroleum asphalt and urea were mixed in a mass ratio of 5:1.
[0136] Comparative Example 10
[0137] The experimental steps were the same as those in Example 14, except that petroleum asphalt and urea were mixed in a mass ratio of 5:1.
[0138] Comparative Example 11
[0139] The experimental steps were the same as in Example 14, but the heat treatment time was 12°C.
[0140] Comparative Example 12
[0141] The experimental steps are the same as those in Example 14, but the heat treatment temperature is 400°C.
[0142] Comparative Example 13
[0143] The experimental steps are the same as those in Example 2, but step S6 is: taking 20 g of the pre-carbonized precursor prepared in step S3 and 3 g of the nitrogen-containing asphalt coating obtained in step S5 and mixing them at high speed.
[0144] Five groups of samples were randomly selected from the finished hard carbon negative electrode materials prepared in the above-mentioned Examples 1-20 and Comparative Examples 1-13, and 2 mg of each group was used to measure the thickness of the coating layer and the carbon layer spacing of the coating layer by transmission electron microscope (TEM). The results are shown in Table 1-2.
[0145] Table 1
[0146]
[0147]
[0148] Table 2
[0149]
[0150] Furthermore, the hard carbon negative electrode materials prepared in the above Examples 1-20 and Comparative Examples 1-13 were used as active substances for the preparation of sodium ion batteries as negative electrode materials: 184 mg of carbon material powder, 6 mg of conductive carbon black, 6 mg of 2% (w / w) carboxymethyl cellulose solution, and 17.5 mg of 40% (w / w) styrene-butadiene rubber were weighed in a mass ratio of 92%:3%:1.5%:3.5%, and an appropriate amount of deionized water was added dropwise. The mixture was stirred for 20 minutes until it became a uniform slurry. A 100 μm scraper was used to evenly coat the mixture on the surface of a copper (Cu) foil, and the mixture was dried in a 105°C forced air drying oven for 2 hours. The Cu foil with the active material was cut into disc-shaped negative electrode sheets, which were then transferred to a glove box for standby use. The assembly of the simulated battery was carried out in a MIKROUNA glove box filled with Ar atmosphere, using the prepared carbon material electrode as the negative electrode, commercial electrolyte 1.0 mol / L NaPF6 / EC:DMC (1:1) (V:V) as the electrolyte, and Na metal sheet as the counter electrode to assemble a 2016 button cell. The battery performance test results are shown in Table 3-6.
[0151] in, Figure 1-3 4-6 are the first charge and discharge curves of the hard carbon negative electrode materials provided in Examples 1, 7 and 12 respectively.
[0152] Table 3
[0153]
[0154]
[0155] Table 4
[0156]
[0157] Table 5
[0158]
[0159] Table 6
[0160]
[0161] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
[0162] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a hard carbon negative electrode material, characterized in that: include: Performing nitrogen doping treatment on asphalt to obtain nitrogen-containing asphalt coating; The pre-carbonized biomass powder and the nitrogen-containing asphalt coating are evenly mixed, and the obtained mixed powder is sintered to obtain a hard carbon negative electrode material.
2. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The step of subjecting asphalt to nitrogen doping to obtain a nitrogen-containing asphalt coating comprises: After the asphalt is crushed, it is treated with plasma to obtain a nitrogen-containing asphalt coating; In the plasma treatment, the nitrogen gas flow rate is 40-100 mL / min, the power is 200-300 W, the reaction temperature is 25-300° C., and the treatment time is 1-2 h.
3. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The step of subjecting asphalt to nitrogen doping to obtain a nitrogen-containing asphalt coating comprises: The asphalt is mixed with a nitrogen source and then subjected to heat treatment to obtain a nitrogen-containing asphalt coating; The amount of nitrogen source is 2-10%, the heat treatment temperature is 200-280° C., and the heat treatment time is 3-6 hours.
4. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The step of subjecting asphalt to nitrogen doping to obtain a nitrogen-containing asphalt coating comprises: The asphalt is mixed with a nitrogen source and then ball-milled, or the asphalt is placed in a nitrogen-containing gas atmosphere and ball-milled to obtain a nitrogen-containing asphalt coating; wherein the nitrogen source amount is 2-10%; when the nitrogen source amount is 2-5%, the ball-milling time is 6-24h, and when the nitrogen source amount is 5-10%, the ball-milling time is 6-12h.
5. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the pre-carbonized biomass powder to the nitrogen-containing asphalt coating is 10:(0.2-1).
6. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: Before the step of uniformly mixing the pre-carbonized biomass powder and the nitrogen-containing asphalt coating and sintering the obtained mixed powder to obtain the hard carbon negative electrode material, the method includes: The biomass is placed in an inert gas atmosphere, pre-carbonized at a temperature of 400-800°C for 2-6 hours, and then crushed.
7. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The mixed powder is sintered to obtain a hard carbon negative electrode material, comprising: The mixed powder is placed in an inert gas atmosphere and sintered at a temperature of 1100-1500° C. for 2-6 hours to obtain a hard carbon negative electrode material.
8. A hard carbon negative electrode material, characterized in that: The hard carbon negative electrode material is prepared by the method for preparing the hard carbon negative electrode material according to any one of claims 1-7.
9. A nitrogen-containing asphalt coating as claimed in claim 1.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the hard carbon negative electrode material according to claim 8.
Citation Information
Patent Citations
High-performance nitrogen-rich carbon composite electrode material and preparation method thereof
CN105185963A
Nitrogen-doped synergistic conductive polymer modified silicon-carbon composite negative electrode material and preparation method thereof
CN114050243A
Preparation method and application of hard carbon material
CN116395667A
Negative electrode material of sodium ion battery, preparation method of negative electrode material, negative electrode plate containing negative electrode material and sodium ion battery
CN117985678A
Composite hard carbon material, preparation method therefor, and use thereof
WO2024109849A1